IZrO transparent conductive film and preparation method and application thereof

By preparing IZrO transparent conductive films, using magnetron cosputtering and heat treatment technology, the problems of high cost and low near-infrared transmittance of existing TCO materials are solved, and a high-performance transparent conductive film used in photovoltaic cells is realized.

CN119553228AActive Publication Date: 2025-03-04WUHU YINGRI TECH CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411762647.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-04
Estimated Expiration
2044-12-03

AI Technical Summary

Technical Problem

Existing transparent conductive oxide (TCO) materials such as indium tin oxide (ITO) are limited in their wide application due to their high cost and low near-infrared transmittance when applied to photovoltaic cells.

Method used

Using an IZrO transparent conductive film, the indium oxide target and the doped zirconia target are prepared by magnetron cosputtering, and then heat treatment is performed to form a thin film with excellent conductivity and high near-infrared transmittance.

Benefits of technology

The IZrO transparent conductive film used in photovoltaic cells has excellent conductivity and high near-infrared transmittance, which improves the performance and application potential of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005168088760000061
    Figure BDA0005168088760000061
  • Figure BDA0005168088760000071
    Figure BDA0005168088760000071
Patent Text Reader

Abstract

The invention relates to the technical field of material science, in particular to an IZrO transparent conductive film and a preparation method and application thereof. According to the IZrO transparent conductive film, an indium oxide target material and a doped zirconium oxide target material are subjected to magnetron co-sputtering to prepare an IZrO film, then the IZrO film is subjected to heat treatment, the IZrO transparent conductive film is flat and uniform in surface and excellent in conductivity and has excellent optical permeability, the transmittance is not lower than 95.4% under 400-1000 nm, and the IZrO transparent conductive film is a transparent conductive film. When the material is applied to a photovoltaic cell, the cell has good response in the wave band of 400-1000 nm, and the cell performance is still kept stable after 1000 h at 85 DEG C and 85% relative humidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material science and technology, and in particular to an IZrO transparent conductive film and a preparation method and application thereof. Background Art

[0002] Transparent conductive oxides (TCO), such as indium tin oxide (ITO), are widely used in photovoltaic cells, displays and other fields.

[0003] Patent document CN108585832A discloses a method for preparing an indium tin oxide target. The method described in the invention is easy to control, reduces the sintering temperature to promote densification, and improves the conductivity of the target. The sintered target has a more uniform composition, low resistivity, and high relative density. Patent document CN114436642A discloses a method for preparing an indium tin oxide alloy target. The application prepares an indium tin oxide alloy target with uniform structure, fine grains, and high heat shock resistance. The alloy target is used as a rotary target for vacuum coating to obtain a high-resistance, anti-electromagnetic interference, anti-static, and wear-resistant high-quality film, which can increase the uniformity of the film layer and improve the utilization rate of the target.

[0004] Although the indium tin oxide targets obtained in the above patents have high density and excellent conductivity, their high cost and low near-infrared transmittance limit their application. Therefore, it is urgent to develop a new type of transparent conductive material. Summary of the invention

[0005] In view of this, the purpose of the present invention is to propose a preparation method of an IZrO transparent conductive film and its application, so as to provide a conductive film with excellent conductive properties and high near-infrared transmittance for use in photovoltaic cells.

[0006] Based on the above purpose, the present invention provides a method for preparing an IZrO transparent conductive film. The preparation method is as follows:

[0007] (1) preparing an IZrO thin film by magnetron co-sputtering an indium oxide target and a doped zirconium oxide target;

[0008] (2) heat treating the IZrO film to obtain an IZrO transparent conductive film;

[0009] The preparation steps of the doped zirconium oxide target in step (1) are as follows:

[0010] The zirconium oxide powder is acid-washed, filtered, and washed to obtain a surface-roughened zirconium oxide powder; the surface-roughened zirconium oxide powder is then mixed with silicon tetrachloride, stirred evenly, allowed to stand for 3-4 hours, filtered, and dried to obtain a doped zirconium oxide powder;

[0011] The doped zirconia powder is ball-milled and then cold isostatically pressed to obtain a green embryo, and finally the green embryo is sintered at a high temperature of 1400° C. to 1650° C. to obtain a doped zirconia target.

[0012] Preferably, the purity of the indium oxide target in step (1) is not less than 99.9%.

[0013] Preferably, the magnetron co-sputtering process in step (1) adopts a DC magnetron sputtering system, and sputtering is performed in a mixed atmosphere of oxygen and argon, wherein the sputtering power is 100-150 W, the flow ratio of oxygen to argon is 1:10, and the vacuum degree is maintained at 1×10 -3 Torr, heating temperature 450-600℃.

[0014] Preferably, the heat treatment in step (2) is carried out at a temperature of 300-500° C. and for a time of 4-6 hours.

[0015] Preferably, the pickling adopts a dilute hydrochloric acid solution with a concentration of 5-8 mol / L.

[0016] Preferably, the usage ratio of the zirconium oxide powder and the dilute hydrochloric acid is 50g:100mL.

[0017] Preferably, the particle size of the zirconium oxide powder is 70-100 μm.

[0018] Preferably, the thickness of the film is 50 nm.

[0019] Furthermore, the present invention also provides an IZrO transparent conductive film, and the IZrO transparent conductive film is prepared by the above-mentioned method for preparing the IZrO transparent conductive film.

[0020] Furthermore, the present invention also provides an application of an IZrO transparent conductive film, wherein the IZrO transparent conductive film is applied to a photovoltaic cell.

[0021] Beneficial effects of the present invention: The present invention performs doping modification on zirconium oxide powder so that silicon is doped into the zirconium oxide powder, and increases the specific surface area of ​​the zirconium oxide powder through surface treatment, thereby allowing more silicon elements to adhere to the surface, and in the subsequent magnetron sputtering process, more silicon oxide can be generated in situ and evenly distributed on the film to form a uniform conductive network, thereby allowing the film to have better conductive properties and better light transmittance.

[0022] The IZrO transparent conductive film obtained by the invention is applied to a photovoltaic cell, and the cell has a good response in the 400nm to 1000nm band, and the cell performance remains stable after 1000h at 85°C and 85% relative humidity. DETAILED DESCRIPTION

[0023] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.

[0024] Embodiment 1: A method for preparing an IZrO transparent conductive film, the specific preparation steps are as follows:

[0025] (1) placing 100 g of zirconium oxide powder with a particle size of 70 μm in 200 ml of a 5 mol dilute hydrochloric acid solution at 50° C. for reaction for 2 h, filtering, washing three times with anhydrous ethanol, and drying for 18 h under vacuum at 30° C. to obtain a surface roughened zirconium oxide powder;

[0026] (2) 100 g of surface roughened zirconium oxide powder and 200 g of silicon tetrachloride were mixed, stirred evenly, allowed to stand for 3 h, filtered, and dried at 40° C. for 20 h to obtain doped zirconium oxide powder;

[0027] (3) 100 g of doped zirconia powder was ball-milled at 400 rpm for 4 h, and then pressed at 100 MPa for 160 s to obtain a green embryo, which was then sintered at 1400 °C for 2 h to obtain a density of 5.2 g / cm 3 Doped zirconia target;

[0028] (4) The doped zirconium oxide target and the indium oxide target were magnetron co-sputtered to obtain a film with a thickness of 50 nm, wherein the power of the magnetron sputtering was 100 W, the flow ratio of oxygen to argon was 1:10, and the vacuum degree was maintained at 1×10 -3 Torr, heating temperature 450℃;

[0029] (5) The film was heat treated at 300°C for 4 h to obtain an IZrO transparent conductive film.

[0030] Embodiment 2: A method for preparing an IZrO transparent conductive film, the specific preparation steps are as follows:

[0031] (1) placing 150 g of zirconium oxide powder with a particle size of 85 μm in 300 ml of a 7 mol dilute hydrochloric acid solution at 75° C. for reaction for 2 h, filtering, washing three times with anhydrous ethanol, and drying at 70° C. under vacuum for 21 h to obtain a surface-roughened zirconium oxide powder;

[0032] (2) 125 g of surface roughened zirconium oxide powder and 250 g of silicon tetrachloride were mixed, stirred evenly, allowed to stand for 4 h, filtered, and dried at 45 ° C. for 22 h to obtain doped zirconium oxide powder;

[0033] (3) 125 g of doped zirconia powder was ball-milled at 550 rpm for 5 h, and then pressed at 125 MPa for 200 s to obtain a green embryo, which was then sintered at 1550 °C for 3 h to obtain a density of 5.3 g / cm 3 Doped zirconia target;

[0034] (4) The doped zirconium oxide target and the indium oxide target were magnetron co-sputtered to obtain a film with a thickness of 50 nm, wherein the power of the magnetron sputtering was 125 W, the flow ratio of oxygen to argon was 1:10, and the vacuum degree was maintained at 1×10 -3 Torr, heating temperature 550℃;

[0035] (5) The film was heat treated at 400°C for 5 h to obtain an IZrO transparent conductive film.

[0036] Embodiment 3: A method for preparing an IZrO transparent conductive film, the specific preparation steps are as follows:

[0037] (1) placing 200 g of zirconium oxide powder with a particle size of 100 μm in 400 ml of a dilute hydrochloric acid solution with a concentration of 8 mol, reacting at 100° C. for 3 h, filtering, washing three times with anhydrous ethanol, and drying at 100° C. in a vacuum state for 24 h to obtain a surface-roughened zirconium oxide powder;

[0038] (2) 150 g of surface roughened zirconium oxide powder and 300 g of silicon tetrachloride were mixed, stirred evenly, allowed to stand for 4 h, filtered, and dried at 50° C. for 24 h to obtain doped zirconium oxide powder;

[0039] (3) 150 g of doped zirconia powder was ball-milled at 700 rpm for 6 h, and then pressed at 150 MPa for 240 s to obtain a green embryo, which was then sintered at 1650 °C for 4 h to obtain a density of 5.4 g / cm 3 Doped zirconia target;

[0040] (4) The doped zirconium oxide target and the indium oxide target were magnetron co-sputtered to obtain a film with a thickness of 50 nm, wherein the power of the magnetron sputtering was 150 W, the flow ratio of oxygen to argon was 1:10, and the vacuum degree was maintained at 1×10 -3 Torr, heating temperature 600℃;

[0041] (5) The film was heat treated at 500°C for 6 h to obtain an IZrO transparent conductive film.

[0042] Comparative Example 1: A method for preparing an IZrO thin film, the specific preparation steps are as follows:

[0043] The difference from Example 2 is that the zirconium oxide powder is not subjected to surface treatment, and the remaining steps are the same as those of Example 2. The specific steps are as follows:

[0044] (1) 125 g of zirconium oxide powder and 250 g of silicon tetrachloride were mixed, stirred evenly, allowed to stand for 4 h, filtered, and dried at 45 ° C. for 22 h to obtain doped zirconium oxide powder;

[0045] (2) 125 g of doped zirconia powder was ball-milled at 550 rpm for 5 h, and then pressed at 125 MPa for 200 s to obtain a green embryo, which was then sintered at 1550 °C for 3 h to obtain a density of 5.3 g / cm 3 Doped zirconia target;

[0046] (3) The doped zirconium oxide target and the indium oxide target were magnetron co-sputtered to obtain a film with a thickness of 50 nm, wherein the power of the magnetron sputtering was 125 W, the flow ratio of oxygen to argon was 1:10, and the vacuum degree was maintained at 1×10 -3 Torr, heating temperature 550℃;

[0047] (4) The film was heat treated at 400°C for 5 h to obtain an IZrO transparent conductive film.

[0048] Comparative Example 2: A method for preparing an IZrO thin film, the specific preparation steps are as follows:

[0049] The difference from the embodiment is that the silicon oxide powder is directly mixed with the silicon dioxide powder and ball milled. The specific preparation steps are as follows:

[0050] (1) placing 150 g of zirconium oxide powder with a particle size of 85 μm in 300 ml of a 7 mol dilute hydrochloric acid solution at 75° C. for reaction for 2 h, filtering, washing three times with anhydrous ethanol, and drying at 70° C. under vacuum for 21 h to obtain a surface-roughened zirconium oxide powder;

[0051] (2) 1 g of surface roughened zirconium oxide powder and 25 g of silicon dioxide powder were ball milled at 550 rpm for 5 h, and then pressed at 125 MPa for 200 s to obtain a green embryo. The green embryo was then sintered at 1550 °C for 3 h to obtain a density of 5.3 g / cm 3 Doped zirconia target;

[0052] (3) The doped zirconium oxide target and the indium oxide target were magnetron co-sputtered to obtain a film with a thickness of 50 nm, wherein the power of the magnetron sputtering was 125 W, the flow ratio of oxygen to argon was 1:10, and the vacuum degree was maintained at 1×10 -3 Torr, heating temperature 550℃;

[0053] (4) The film was heat treated at 400°C for 5 h to obtain an IZrO transparent conductive film.

[0054] Comparative Example 3: A method for preparing an IZrO thin film, the specific preparation steps are as follows:

[0055] (1) 100 g of zirconium oxide powder and 25 g of silicon dioxide powder were ball-milled at 550 rpm for 5 h, and then pressed at 125 MPa for 200 s to obtain a green embryo. The green embryo was then sintered at 1550 °C for 3 h to obtain a density of 5.3 g / cm 3 Doped zirconia target;

[0056] (2) The doped zirconium oxide target and the indium oxide target were magnetron co-sputtered to obtain a film with a thickness of 50 nm, wherein the power of the magnetron sputtering was 125 W, the flow ratio of oxygen to argon was 1:10, and the vacuum degree was maintained at 1×10 -3 Torr, heating temperature 550℃;

[0057] (3) The film was heat treated at 400°C for 5 h to obtain an IZrO transparent conductive film.

[0058] Performance Testing

[0059] The surface roughness of the film was observed by AFM, and the test results are shown in Table 1;

[0060] The conductivity and mobility of the film were tested according to the Hall effect, and the test results are shown in Table 1;

[0061] The optical transmittance of the film was measured by UV-Vis-NIR spectrophotometer with a test wavelength of 400-1000 nm. The test results are shown in Table 1.

[0062] Table 1 Performance test results

[0063]

[0064]

[0065] The sample obtained in Example 2 was used as the front electrode of an n-type silicon-based photovoltaic cell with a cell structure of n-Si / IZrO / Ag. The prepared cell sample was tested:

[0066] The IV curve test shows that the open circuit voltage of the battery is 0.6V and the short circuit current density is 35mA / cm 2 , the fill factor is 0.75 and the conversion efficiency reaches 16.5%;

[0067] The EQE curve test shows that the battery has a good response in the 400nm to 1000nm band;

[0068] Stability tests show that the battery performance remains stable after 1000 hours at 85°C and 85% relative humidity.

[0069] Data analysis: It can be seen from Examples 1-3 in Table 1 that the IZrO transparent conductive film of the present invention has a flat and uniform surface and excellent conductive performance, and its resistivity can reach as low as 4×10 -5 Ω·cm, and the carrier concentration can reach 4.5×10 20 cm -3 , the mobility can reach 28cm 2 / Vs, and most importantly, it has excellent optical transmittance, with a transmittance of no less than 95.4% at 400-1000nm.

[0070] It can be seen from Example 2 and Comparative Example 1 in Table 1 that the present invention increases the specific surface area of ​​the zirconium oxide powder by surface treatment of the zirconium oxide powder, thereby allowing more silicon elements to adhere to the surface. In the subsequent magnetron sputtering process, more silicon oxide can be generated in situ and evenly distributed on the film to form a uniform conductive network. In addition, silicon dioxide itself has excellent light transmittance, which can improve the light transmittance of the film.

[0071] It can be seen from Example 2 and Comparative Example 2 in Table 1 that the present invention can make silicon dioxide evenly distributed in the film through doping and then in-situ generation to form a coherent conductive network, so that the conductivity of the target material is further improved and the light transmittance of the film is improved to a certain extent.

[0072] It can be seen from Example 2 and Comparative Example 3 in Table 1 that the conductivity of the target material is improved by surface treating the zirconium oxide powder and then performing doping modification, and the conductivity of the film obtained by sputtering is better and the light transmittance of the film is better. When applied to photovoltaic cells, the cell has a good response in the 400nm to 1000nm band, and at 85°C and 85% relative humidity, the cell performance remains stable after 1000h.

[0073] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.

Claims

1. A method for preparing an IZrO transparent conductive film, characterized in that: The preparation method is as follows: (1) preparing an IZrO thin film by magnetron co-sputtering an indium oxide target and a doped zirconium oxide target; (2) heat treating the IZrO film to obtain an IZrO transparent conductive film; The preparation steps of the doped zirconium oxide target in step (1) are as follows: The zirconium oxide powder is acid-washed, filtered, and washed to obtain a surface-roughened zirconium oxide powder; the surface-roughened zirconium oxide powder is then mixed with silicon tetrachloride, stirred evenly, allowed to stand for 3-4 hours, filtered, and dried to obtain a doped zirconium oxide powder; The doped zirconia powder is ball-milled and then cold isostatically pressed to obtain a green embryo, and finally the green embryo is sintered at a high temperature of 1400° C. to 1650° C. to obtain a doped zirconia target.

2. The method for preparing the IZrO transparent conductive film according to claim 1, characterized in that: The purity of the indium oxide target material in step (1) is not less than 99.9%.

3. The method for preparing the IZrO transparent conductive film according to claim 1, characterized in that: The magnetron co-sputtering process in step (1) uses a DC magnetron sputtering system to perform sputtering in a mixed atmosphere of oxygen and argon, wherein the sputtering power is 100-150 W, the flow ratio of oxygen to argon is 1:10, and the vacuum degree is maintained at 1×10 -3 Torr, heating temperature 450-600℃.

4. The method for preparing the IZrO transparent conductive film according to claim 1, characterized in that: The heat treatment in step (2) is performed at a temperature of 300-500° C. and for a time of 4-6 hours.

5. The method for preparing the IZrO transparent conductive film according to claim 1, characterized in that: The acid washing adopts a dilute hydrochloric acid solution with a concentration of 5-8 mol / L.

6. The method for preparing the IZrO transparent conductive film according to claim 1, characterized in that: The dosage ratio of the zirconium oxide powder to the diluted hydrochloric acid is 50g:100mL.

7. The method for preparing the IZrO transparent conductive film according to claim 1, characterized in that: The particle size of the zirconium oxide powder is 70-100 μm.

8. An IZrO transparent conductive film, characterized in that: The IZrO transparent conductive film is prepared by the method for preparing the IZrO transparent conductive film according to any one of claims 1 to 8.

9. An application of the IZrO transparent conductive film according to claim 8, characterized in that: The IZrO transparent conductive film is applied to photovoltaic cells.

Citation Information

Patent Citations

  • Preparation method of indium tin oxide target

    CN108585832A

  • Preparation method of indium tin oxide alloy target material

    CN114436642A

  • Shield layer, method for producing shield layer, and oxide sputtering target

    CN111902561A

  • Conductive member and method for manufacturing conductive member

    CN118556273A

  • Manufacturing method of transparent conductive film and transparent conductive film

    JP2008059928A